TINJAUAN VISUAL TERHADAP ILUSTRASI KEMASAN BOTOL AQUA 600ML “LABEL KHUSUS TEMUKAN INDONESIAMU” - Febriani Saputri; hendra afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
This study was created by the writer with the aim of describing the meaning and also the cultural values contained in the Aqua packaging illustration of the special label "Discover Your Indonesia".The research method used by researchers is a type of descriptive qualitative method with literature study data collection techniques where the data used is obtained from various journal and internet book sources. This study focuses on the visual analysis of illustrations, colors, and characters on objects contained in the Aqua packaging of the special label "Discover Your Indonesia" reviewed with theories relating to color illustrations and perceptions. Researchers describe the cutouts of each object on the illustration in tabular form and are identified to explain each meaning contained in the Aqua packaging illustration of the special label "Find Your Indonesia"The results of this study explain that every illustration that is on the Aqua label special label "Discover Indonesia" has a positive meaning with the contents of the message delivered to apply Indonesian culture in everyday life.Keywords: Illustration, Visual Overview, Aqua